A dynamic histone-based chromatin regulatory toolkit underpins genome and developmental evolution in an invertebrate clade - Francisco M. Martín-Zamora; Joby Cole; Rory D. Donnellan; Kero Guynes; Allan M. Carrillo-Baltodano; Mark J. Dickman; Paul J. Hurd; José M. Martín-Durán (Genome Biology)
Abstract Background The dynamic addition and removal of posttranslational modifications on eukaryotic histones define regulatory regions that play a central role in genome and chromatin biology. However, our understanding of these regulatory mechanisms in animals is primarily based on a few model systems, preventing a general understanding of how histone-based regulation directs and promotes phenotypic variation during animal embryogenesis. Results Here, we apply a comprehensive multi-omics approach to dissect the histone-based regulatory complement in Annelida, one of the largest invertebrate clades. Annelids exhibit a conserved histone repertoire organized in clusters of dynamically regulated, hyperaccessible chromatin. However, unlike other animals with reduced genomes, the worm Dimorphilus gyrociliatus shows a dramatically streamlined histone repertoire, revealing that genome compaction has lineage-specific effects on histone-based regulation. Notably, the annelid Owenia fusiformis has two H2A.X variants that co-occur in other animals, sometimes associate with fast cell divisions, and represent a unique case of widespread parallel evolution of a histone variant in Eukarya. Histone-modifying enzyme complements are largely conserved among annelids. Yet, temporal differences in the expression of a reduced set of histone modifiers correlate with distinct ontogenetic traits and variation in the adult landscapes of histone posttranslational modifications, as revealed by quantitative mass spectrometry in O. fusiformis and Capitella teleta. Conclusions Our analysis of histone-based epigenetics within a non-model phylum informs the evolution of histone-based regulation, presenting a framework to explore how this fundamental genome regulatory layer generally contributes to developmental and morphological diversification in annelids and animals.